A Method To Ensure Heterogeneous Mixing of Grade 9 Classes Bruce Brydges. - Brydges, Bruce (Distributed by ERIC Clearinghouse, 1993)
This paper presents outcomes of a practicum that was designed to address a need that was created when the Ministry of Education in Ontario, Canada, mandated that all grade 9 classes be "destreamed." A review of educational literature found no methods for ensuring that classes are truly heterogeneously mixed. The practicum was designed to gather data on each student entering grade 9 in order to ensure that classes were mixed according to the following variables: academic ability, gender, special-education identification, and feeder school of origin. Using a holistic scoring rubric, mean scores and standard deviations were developed to guide the placement of students in a timetable designed to support heterogeneously mixed student cohorts. The plan was implemented in a large, modern, rural, composite secondary school in Ontario (Canada). Findings demonstrated that heterogeneous mixing could be achieved for core classes; however, students tended to stream themselves through the choice of optional subjects. Four tables are included. Appendices contain the holistic rating scale, the grade 9 student timetable, and a sample database setup for Lotus 1-2-3. Contains 34 references. (Author/LMI)